Analiza (ne)vzdržnosti javnih financ v Sloveniji - Dolenc, Primož (Naše gospodarstvo, 2006)
In the immediate period before adopting the euro, many debates in Slovenia deal with fulfillment of the Maastricht criteria. Slovenia has never had any significant problems with the fiscal criteria, but this does not mean that it has a long-term sustainable fiscal situation. The purpose of the analysis is exactly that: to analyze the (non)sustainability of Slovenia's fiscal stance. The methodology is based on an objective analysis of the long-term stability/sustainability of public finance. The analysis shows that Slovenia crossed the acceptable level of sustainability in previous years. In the coming years the circumstances can only worsen unless necessary fiscal reform and other measures (especially reform of public-debt management) are introduced.
Keywords: Slovenia; Slovenija; public finance; javne finance; davčna politika; proračun; javni dohodki; javni izdatki; javni dolg